Using the Internet System for Online Learning of Undergraduate Student Faculty of Education Sakon Nakhon Rajabhat University - raksapakdee, chuleewan; Srihirun, Wason; Jeenakarn, Itchaya; Srihirun, Supawadee (An Online Journal of Education, 2024)
The objectives of this research were to Study the use of the Internet system. Opinions on the use of the Internet and problems in online learning of undergraduate students. The sample used in the research was undergraduate students from the Faculty of Education, Sakon Nakhon Rajabhat University. Currently studying in the first semester of academic year 2022, a total of 361 students are randomly selected in multiple stages. The tools used in the research are questionnaires. The data were analyzed by breaking down the frequency, determining the percentage, mean, standard deviation and content analysis. The results showed that: 1) The use of the Internet system for online learning of students is mainly incurred. Experience in using the Internet and often speaking Thai. The use of the Internet for education is very high (M = 3.90, SD = 0.33) and the use of the Internet for research is very high (M = 3.93, SD = 0.38). 2) Students’ opinions on the use of the Internet in online learning. It was found that the university’s internet system was not as smooth as it should affect online learning. Some lecturers do not have online teaching preparation and the space on campus is not enough to use the Internet and 3) Problems in using the internet for online learning. The server computer is inefficient, there are frequent delays, English is also a barrier for students to use the Internet, and some instructors do not pay attention to online learning.